SUN’IY INTELLEKT MUHITIDA OLIY TA’LIM MUASSASALARIDA NAZARIY VA EKSPERIMENTAL FIZIKANI O‘QITISHNING DIDAKTIK MODELINI TAKOMILLASHTIRISH METODIKASI (Kasb-Hunar Ta'limi, 2026)
This article discusses the improvement of the didactic model for theoretical and experimental physics teaching in higher education institutions using artificial intelligence technologies. The study analyzes the possibilities of personalizing the learning process, increasing interactivity, and achieving deep knowledge assimilation based on neural networks. The authors propose a pedagogical-methodological model, demonstrating that the integration of artificial intelligence tools significantly enhances the effectiveness of physics education